Melanopsin Retinal Ganglion Cells and Pupil: Clinical Implications for Neuro-Ophthalmology - La Morgia, Chiara; Carelli, Valerio; Carbonelli, Michele (Frontiers in Neurology, 2018)
Melanopsin retinal ganglion cells (mRGCs) are intrinsically photosensitive RGCs that mediate many relevant non-image forming functions of the eye, including the pupillary light reflex, through the projections to the olivary pretectal nucleus. In particular, the post-illumination pupil response (PIPR), as evaluated by chromatic pupillometry, can be used as a reliable marker of mRGC function in vivo. In the last years, pupillometry has become a promising tool to assess mRGC dysfunction in various neurological and neuro-ophthalmological conditions. In this review we will present the most relevant findings of pupillometric studies in various neuro-ophthalmological conditionsincluding hereditary optic neuropathies, glaucoma, ischemic optic neuropathies, idiopathic intracranial hypertension, multiple sclerosis and Parkinson’s disease. The use of PIPR as a marker for mRGC function is also proposed for other neurodegenerative disorders in which circadian dysfunction is documented.